Ceramic and carbonaceous reinforced carbon-based composite bipolar plate material as well as preparation method and application thereof

By using heat condensation reaction and hot-pressing forming technology of ceramic and carbonaceous reinforced phase and asphalt compounds in composite carbon-based bipolar plate materials, the problem of poor performance of existing materials has been solved, and significant improvements in mechanical properties, conductive properties and corrosion resistance have been achieved.

CN119899042AActive Publication Date: 2025-04-29CHINA ENFI ENG CORP +1

Patent Information

Application Number
CN202510378313.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-29
Estimated Expiration
2045-03-28

AI Technical Summary

Technical Problem

The mechanical properties, conductive properties and electrochemical corrosion resistance of existing composite carbon-based bipolar plate materials are poor.

Method used

By mixing the ceramic reinforced phase, carbonaceous reinforced phase and asphalt compounds for heat condensation reaction, a precursor of ceramic and carbonaceous reinforced phase is formed by mixing the ceramic and carbonaceous reinforced phases in situ, and then undergoing hot pressing, sintering and carbonaceous reinforced carbon matrix composite bipolar plate material is prepared.

Benefits of technology

The mechanical properties, conductive properties and electrochemical corrosion resistance of bipolar plate materials have been significantly improved, and a more uniform and tight composite structure has been achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119899042A_ABST
    Figure CN119899042A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of inorganic non-metallic materials, in particular to a ceramic and carbonaceous reinforced carbon-based composite bipolar plate material and a preparation method and application thereof. The preparation method of the ceramic and carbonaceous reinforced carbon-based composite bipolar plate material comprises the following steps: uniformly mixing a ceramic reinforced phase, a carbonaceous reinforced phase and an asphalt compound as raw materials, carrying out a thermal polycondensation reaction, and carrying out solvent extraction and solid-liquid separation to obtain an asphalt mesocarbon microbead in-situ coated ceramic and carbonaceous reinforced phase precursor; carrying out hot press molding on the pitch mesocarbon microbead in-situ coated ceramic and the carbonaceous reinforced phase precursor to obtain a green body; and carrying out sintering carbonization treatment and dipping treatment on the green body to obtain the ceramic and carbonaceous reinforced carbon-based composite bipolar plate material. The ceramic and carbonaceous reinforced carbon-based composite bipolar plate material with excellent mechanical properties, conductivity and electrochemical corrosion resistance is prepared through a low-cost, short-process and efficient process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of inorganic non-metallic material preparation, and in particular to ceramic and carbonaceous reinforced carbon-based composite bipolar plate materials and preparation methods and applications thereof. Background Art

[0002] Proton exchange membrane fuel cell (PEMFC) is a power generation device that converts chemical energy stored in fuel and oxidant directly into electrical energy without combustion. As the main component of proton exchange membrane fuel cells, the material and performance of the bipolar plate directly determine the performance, operating life and preparation cost of the battery stack. Carbon-based materials have good electrical and thermal conductivity and corrosion resistance, and are widely used as bipolar plates for proton exchange membrane fuel cells. However, as bipolar plate materials, they generally have problems such as high porosity, poor processing mechanical properties, high resistivity, and easy electrochemical oxidation corrosion.

[0003] Composite carbon-based bipolar plate materials are composite materials with organic carbon precursors such as polymer resins, asphalt, and mesophase carbon microspheres as bonding phases, and carbonaceous materials (such as graphite, carbon fiber, and graphene) or ceramic materials (such as silicon carbide, boron carbide, etc.) as reinforcing phases. Among them, when mesophase carbon microspheres (MCMB) are used as carbon matrix and bonding phases and reinforcing phases, they are mainly bonded and composited by mixing the mesophase carbon microspheres with the reinforcing phases and performing hot pressing, sintering and other steps. However, the reinforcing phase particles and the mesophase carbon microspheres are still independent individuals, and there are problems such as raw material agglomeration, uneven composite, and insufficient bonding between the two phases, resulting in a small contact area between the particles and large pores, which seriously affect the mechanical and electrochemical properties of the material. Therefore, how to prepare a carbon-based composite bipolar plate material with excellent mechanical properties, electrical conductivity, and electrochemical corrosion resistance is still an urgent problem to be solved. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the defects of existing composite carbon-based bipolar plate materials in terms of poor mechanical properties, electrical conductivity and electrochemical corrosion resistance, thereby providing a ceramic and carbon-reinforced carbon-based composite bipolar plate material and its preparation method and application that solve the above problems.

[0005] In order to achieve the above object, the present invention provides the following technical solutions: In a first aspect, the present invention provides a method for preparing a ceramic and carbonaceous reinforced carbon-based composite bipolar plate material, comprising: The ceramic reinforcement phase, the carbonaceous reinforcement phase and the asphalt compound are mixed as raw materials and subjected to thermal polycondensation reaction, and the asphalt intermediate phase carbon microspheres in-situ coated with ceramic and carbonaceous reinforcement phase precursors are obtained through solvent extraction and solid-liquid separation; In-situ coating of the pitch mesophase carbon microspheres with ceramic and carbonaceous reinforcement phase precursors is performed by hot pressing to obtain a green body; The green body is subjected to sintering carbonization treatment and impregnation treatment to obtain ceramic and carbonaceous reinforced carbon-based composite bipolar plate material.

[0006] Preferably, the asphalt compound includes at least one of coal asphalt, petroleum asphalt, naphthalene asphalt, and secondary refined asphalt; And / or, the carbonaceous reinforcement phase includes at least one of graphite, expanded graphite, carbon black, carbon fiber, and graphene; and / or, the particle size of the carbonaceous reinforcement phase is 0.02-10 µm; And / or, the ceramic reinforcement phase includes at least one of titanium boride, titanium carbide, titanium nitride and boron carbide; And / or, the particle size of the ceramic reinforcement phase is 0.1-10 µm; And / or, the mass ratio of the asphalt compound, the ceramic reinforcement phase and the carbonaceous reinforcement phase is 20:(1-6):(0.1-3).

[0007] Preferably, the mixing process is: treating at a temperature of 120-180°C and a stirring rate of 1500-2500 r / min for 0.5-2 h; And / or, the temperature of the thermal polycondensation reaction is 380-420°C; And / or, the heating rate of the thermal polycondensation reaction is 1-5°C / min; And / or, the stirring rate of the thermal polycondensation reaction is 300-800 r / min; And / or, the duration of the thermal polycondensation reaction is 2 to 4 hours; And / or, the atmosphere of the thermal polycondensation reaction is an inert atmosphere; And / or, an asphalt modifier is also added during the thermal polycondensation reaction; the asphalt modifier is a resin-based modifier, preferably at least one of a phenolic resin and an epoxy resin; the mass ratio of the asphalt modifier to the asphalt compound is (0.5-4):20; and / or, crushing is performed after the thermal polycondensation reaction; and / or, the organic solvent used in the solvent extraction includes at least one of tetrahydrofuran, toluene, pyridine, quinoline, dichloromethane, trichloroethylene, and washing oil; And / or, the solid-liquid separation includes at least one of filtration, sedimentation, and centrifugation.

[0008] Preferably, the molding temperature of the hot pressing molding is 320-380°C; And / or, the molding pressure of the hot pressing molding is 30-80 MPa; And / or, the stabilization time of the hot pressing molding is 8 to 15 minutes; And / or, screening is performed before the hot pressing; optionally, the mesh number of the screening is 300 meshes.

[0009] Preferably, the sintering and carbonization treatment process is: firstly heating to 400-450°C at a rate of 1-5°C / min and keeping warm for 1-2 hours, then continuing to heating to 900-1400°C at a rate of 1-2°C / min and keeping warm for 2-5 hours; And / or, the atmosphere of the sintering and carbonization treatment is an inert atmosphere.

[0010] Preferably, the impregnating agent used in the impregnation process is a thermosetting phenolic resin and / or asphalt; And / or, the immersion treatment is carried out under negative pressure; the negative pressure condition is 0.1-10 kPa; And / or, the immersion treatment time is 5 to 10 hours; and / or, washing with an organic solvent after the immersion treatment; And / or, the impregnation treatment is further followed by a curing treatment.

[0011] Preferably, the organic solvent comprises at least one of ethanol and acetone; And / or, when the impregnating agent is a thermosetting phenolic resin, the curing temperature is 160-190° C., and the curing time is 1-2 h; And / or, when the impregnating agent is asphalt, the content of asphalt quinoline insoluble matter is not greater than 0.1%, the softening point is 50-100°C, the temperature of the impregnation treatment is 100-120°C, the temperature of the curing treatment is 380-420°C, and the time of the curing treatment is 2-3h.

[0012] In a second aspect, the present invention further provides a ceramic and carbonaceous reinforced carbon-based composite bipolar plate material, which is prepared by the above-mentioned method for preparing the ceramic and carbonaceous reinforced carbon-based composite bipolar plate material.

[0013] In a third aspect, the present invention also provides the application of the above-mentioned ceramic and carbonaceous reinforced carbon-based composite bipolar plate materials in fuel cells and water electrolysis hydrogen production stacks.

[0014] The technical solution of the present invention has the following advantages: 1. A method for preparing a ceramic and carbonaceous reinforced carbon-based composite bipolar plate material, comprising: mixing ceramic reinforcement phase, carbonaceous reinforcement phase and asphalt compounds as raw materials and performing a thermal polycondensation reaction, obtaining asphalt mesophase carbon microspheres in-situ coated ceramic and carbonaceous reinforcement phase precursors through solvent extraction and solid-liquid separation; hot pressing the asphalt mesophase carbon microspheres in-situ coated ceramic and carbonaceous reinforcement phase precursors to obtain a green body; sintering carbonization treatment and impregnation treatment of the green body to obtain a ceramic and carbonaceous reinforced carbon-based composite bipolar plate material. The present invention uses ceramic and carbonaceous as reinforcement phases, mesophase carbon microspheres obtained by thermal polycondensation of asphalt compounds as binding phases, and in-situ generation of a structure having mesophase carbon microspheres coated with reinforcement phases by using the reinforcement phase as the heterogeneous nucleation core of the thermal polycondensation reaction, so that the carbon matrix (mesophase carbon microspheres generated by thermal polycondensation of asphalt) and the reinforcement phase (ceramic and carbonaceous) form a more uniform and compact composite structure, thereby significantly improving the mechanical and electrochemical properties of the bipolar plate material. Combining the above technical means, the present invention prepares a carbon-based composite bipolar plate material with excellent mechanical properties, electrical conductivity and electrochemical corrosion resistance through a low-cost, short-process and efficient process.

[0015] 2. In the preparation method of the ceramic and carbonaceous reinforced carbon-based composite bipolar plate material of the present invention, the ceramic reinforcement phase is preferably titanium boride, which has good electrical conductivity and catalytic graphitization during the carbonization process of the mesophase carbon microsphere precursor, thereby significantly improving the electrical conductivity and electrochemical corrosion resistance of the carbon-based bipolar plate. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 This is a SEM morphology of the asphalt mesophase carbon microspheres in-situ coated with ceramic and carbonaceous reinforcement phase precursor obtained after filtration and separation in Example 1 of the present invention; Figure 2 This is a SEM morphology image of the ceramic and carbonaceous reinforced carbon-based composite bipolar plate material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0018] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0019] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0020] Example 1 This embodiment provides a method for preparing a ceramic and carbonaceous reinforced carbon-based composite bipolar plate material, and the specific steps are as follows: 100 g of medium-temperature coal tar pitch, 5 g of phenolic resin, 10 g of titanium boride with a particle size of 5 µm and 5 g of graphite with a particle size of 3 µm were weighed and mixed uniformly, then placed in a high-temperature reactor and heated to 150 °C. After the asphalt was completely melted, it was dispersed at a high speed of 1500 r / min for 0.5 h. Under argon protection and a stirring rate of 500 r / min, the temperature was raised to 400 °C at 5 °C / min and kept for 2 h for thermal polycondensation reaction. After cooling, a composite mesophase asphalt was obtained. After crushing, a Soxhlet extractor was used with tetrahydrofuran as the solvent to extract the soluble components in the composite mesophase asphalt until the solvent was almost colorless. After filtration and separation, the asphalt mesophase carbon microspheres in situ coated with ceramics and carbonaceous reinforcement phase precursors were obtained. The SEM morphology is shown in FIG. Figure 1 As shown; after the precursor is passed through a 300-mesh sieve, 15 g is weighed and loaded into a mold, and the temperature is raised to 350 ° C under a preload pressure of 2 MPa, and the pressure is increased to 40 MPa, and the pressure is maintained for 10 min to obtain a bipolar plate green body; the green body is laid flat and buried in a crucible filled with graphite fragments, and the temperature is raised to 400 ° C at 5 ° C / min in an inert atmosphere protection condition in a high-temperature furnace, and the temperature is maintained for 1 h; the temperature is continued to be raised to 900 ° C at 2 ° C / min, and the temperature is maintained for 2 h to complete carbonization; the carbonized composite bipolar plate sample is immersed in a thermosetting phenolic resin, placed in a vacuum drying oven, immersed for 5 h under room temperature and 10 kPa negative pressure, and the residual resin on the surface is cleaned with ethanol solvent. After that, it is placed in a heating furnace and heated to 160 ° C. After 2 h of heat preservation, a ceramic and carbonaceous reinforced carbon-based composite bipolar plate material is obtained, and the SEM morphology is as shown Figure 2 shown.

[0021] Example 2 This embodiment provides a method for preparing a ceramic and carbonaceous reinforced carbon-based composite bipolar plate material, and the specific steps are as follows: 100 g of medium-temperature coal tar pitch, 10 g of phenolic resin, 15 g of titanium boride with a particle size of 5 µm, 10 g of graphite with a particle size of 5 µm and 3 g of conductive carbon black were weighed and mixed uniformly, then placed in a high-temperature reactor and heated to 150 °C. After the asphalt was completely melted, it was dispersed at a high speed of 1500 r / min for 0.5 h. Under argon protection and a stirring rate of 500 r / min, the temperature was raised to 400 °C at a rate of 5 °C / min and kept for 2 h for thermal polycondensation reaction. After cooling, a composite mesophase asphalt was obtained. After crushing, a Soxhlet extractor was used with tetrahydrofuran as the solvent to extract the soluble components in the composite mesophase asphalt until the solvent was almost colorless. After filtration and separation, the asphalt mesophase carbon microspheres in-situ coated with ceramic and carbonaceous reinforcement phase precursors were obtained. After the precursor was passed through a 300-mesh sieve, 15 g was weighed and loaded into a mold. The temperature was raised to 350 °C under a preload pressure of 2 MPa and pressurized to 60 MPa, and maintain the pressure for 10 min to obtain a bipolar plate green body; the green body is laid flat and buried in a crucible filled with graphite fragments, and under the protection of an inert atmosphere in a high-temperature furnace, the temperature is raised to 400 ℃ at a rate of 5 ℃ / min and maintained for 1 h; the temperature is further raised to 1000 ℃ at a rate of 2 ℃ / min and maintained for 2 h to complete carbonization; the carbonized composite bipolar plate sample is immersed in a thermosetting phenolic resin, placed in a vacuum drying oven, immersed for 5 h under a negative pressure of 10 kPa at room temperature, and the residual resin on the surface is cleaned with an ethanol solvent, and then placed in a heating furnace and heated to 160 ℃. After 2 h of heat preservation, a ceramic and carbonaceous reinforced carbon-based composite bipolar plate material is obtained.

[0022] Example 3 This embodiment provides a method for preparing a ceramic and carbonaceous reinforced carbon-based composite bipolar plate material, and the specific steps are as follows: 100 g of medium-temperature coal tar pitch, 10 g of phenolic resin, 15 g of titanium boride with a particle size of 5 µm, 5 g of graphite with a particle size of 5 µm and 5 g of expanded graphite with a particle size of 10 µm were weighed and mixed uniformly, then placed in a high-temperature reactor and heated to 150 °C. After the asphalt was completely melted, it was dispersed at a high speed of 1500 r / min for 0.5 h. Under argon protection and a stirring rate of 500 r / min, the temperature was raised to 380 °C at a rate of 5 °C / min and kept for 2 h for thermal polycondensation reaction. After cooling, a composite mesophase asphalt was obtained. After crushing, a Soxhlet extractor was used with tetrahydrofuran as the solvent to extract the soluble components in the composite mesophase asphalt until the solvent was almost colorless. After filtration and separation, the asphalt mesophase carbon microspheres in-situ coated with ceramic and carbonaceous reinforcement phase precursors were obtained. After the precursor was passed through a 300-mesh sieve, 15 g was weighed and loaded into a mold, and the temperature was raised to 350 °C under a preload pressure of 2 MPa. ℃, pressurized to 80 MPa, and maintained at pressure for 10 min to obtain a bipolar plate green body; the green body was laid flat and buried in a crucible filled with graphite fragments, and heated to 400 ℃ at 5 ℃ / min under inert atmosphere protection in a high-temperature furnace, and maintained at this temperature for 1 h; the temperature was further increased to 1200 ℃ at 2 ℃ / min, and maintained at this temperature for 2 h to complete carbonization; the carbonized composite bipolar plate sample was immersed in thermosetting phenolic resin, placed in a vacuum drying oven, immersed for 5 h under negative pressure of 10 kPa at room temperature, and the residual resin on the surface was cleaned with ethanol solvent, and then placed in a heating furnace and heated to 160 ℃, and maintained at this temperature for 2 h to complete curing to obtain a ceramic and carbonaceous reinforced carbon-based composite bipolar plate material.

[0023] Example 4 This embodiment provides a method for preparing a ceramic and carbonaceous reinforced carbon-based composite bipolar plate material, and the specific steps are as follows: 100 g of medium-temperature coal tar pitch, 10 g of phenolic resin, 20 g of titanium boride with a particle size of 3 µm and 1 g of nanocarbon fiber were weighed and mixed uniformly, then placed in a high-temperature reactor and heated to 150 °C. After the asphalt was completely melted, it was dispersed at a high speed of 1500 r / min for 0.5 h. Under argon protection and a stirring rate of 500 r / min, the temperature was raised to 400 °C at a rate of 5 °C / min and kept for 2 h for thermal polycondensation reaction. After cooling, a composite mesophase asphalt was obtained. After crushing, a Soxhlet extractor was used with tetrahydrofuran as the solvent to extract the soluble components in the composite mesophase asphalt until the solvent was almost colorless. After filtration and separation, the asphalt mesophase carbon microspheres in-situ coated with ceramic and carbonaceous reinforcement phase precursors were obtained. After the precursor was passed through a 300-mesh sieve, 15 g was weighed and loaded into a mold. The temperature was raised to 350 °C under a preload pressure of 2 MPa, pressurized to 60 MPa, and kept at a pressure of 10 min to obtain a bipolar plate green body; the green body is laid flat and buried in a crucible filled with graphite fragments, and the temperature is raised to 400 °C at 5 °C / min under inert atmosphere protection in a high-temperature furnace, and kept warm for 1 h; the temperature is further raised to 1200 °C at 2 °C / min, and kept warm for 2 h to complete carbonization; the carbonized composite bipolar plate sample is immersed in thermosetting phenolic resin, placed in a vacuum drying oven, immersed for 5 h under negative pressure of 10 kPa at room temperature, and the residual resin on the surface is cleaned with ethanol solvent, and then placed in a heating furnace and heated to 160 °C, and kept warm for 2 h to complete curing to obtain a ceramic and carbonaceous reinforced carbon-based composite bipolar plate material.

[0024] Example 5 This embodiment provides a method for preparing a ceramic and carbonaceous reinforced carbon-based composite bipolar plate material, and the specific steps are as follows: 100 g of medium-temperature coal tar pitch, 5 g of epoxy resin, 5 g of titanium boride with a particle size of 3 µm and 15 g of graphite with a particle size of 5 µm were weighed and mixed uniformly, then placed in a high-temperature reactor and heated to 120 °C. After the asphalt was completely melted, it was dispersed at a high speed of 1500 r / min for 2 h. Under argon protection and a stirring rate of 300 r / min, the temperature was raised to 380 °C at a rate of 1 °C / min and kept for 4 h for thermal polycondensation reaction. After cooling, a composite mesophase asphalt was obtained. After crushing, a Soxhlet extractor was used with dichloromethane as the solvent to extract the soluble components in the composite mesophase asphalt until the solvent was almost colorless. After centrifugal separation, the asphalt mesophase carbon microspheres in-situ coated with ceramic and carbonaceous reinforcement phase precursors were obtained. After the precursor was passed through a 300-mesh sieve, 15 g was weighed and loaded into a mold. The temperature was raised to 320 °C under a preload pressure of 2 MPa, pressurized to 80 MPa, and kept at a pressure of 8 min to obtain a bipolar plate green body; the green body is laid flat and buried in a crucible filled with graphite fragments, and the temperature is raised to 400 °C at 1 °C / min under inert atmosphere protection in a high-temperature furnace, and kept warm for 1 h; the temperature is further raised to 900 °C at 2 °C / min, and kept warm for 5 h to complete carbonization; the carbonized composite bipolar plate sample is immersed in a thermosetting phenolic resin, placed in a vacuum drying oven, immersed for 10 h under a negative pressure of 10 kPa at room temperature, and the residual resin on the surface is cleaned with acetone solvent, and then placed in a heating furnace and heated to 190 °C. After the curing is completed, a ceramic and carbonaceous reinforced carbon-based composite bipolar plate material is obtained.

[0025] Example 6 This embodiment provides a method for preparing a ceramic and carbonaceous reinforced carbon-based composite bipolar plate material, and the specific steps are as follows: 100 g of petroleum asphalt, 20 g of phenolic resin, 20 g of titanium boride with a particle size of 8 µm and 2 g of conductive carbon black with a particle size of 0.02 µm were weighed and mixed uniformly, then placed in a high-temperature reactor and heated to 180 °C. After the asphalt was completely melted, it was dispersed at a high speed of 2500 r / min for 1 h. Under argon protection and a stirring rate of 800 r / min, the temperature was raised to 420 °C at a rate of 5 °C / min and kept for 2 h for thermal polycondensation reaction. After cooling, a composite mesophase asphalt was obtained. After crushing, a Soxhlet extractor was used with tetrahydrofuran as the solvent to extract the soluble components in the composite mesophase asphalt until the solvent was almost colorless. After filtration and separation, the asphalt mesophase carbon microspheres in-situ coated with ceramic and carbonaceous reinforcement phase precursors were obtained. After the precursor was passed through a 300-mesh sieve, 15 g was weighed and loaded into a mold. The temperature was raised to 380 °C under a preload pressure of 2 MPa, pressurized to 30 MPa, and kept at a pressure of 15 min to obtain a bipolar plate green body; the green body is laid flat and buried in a crucible filled with graphite fragments, and the temperature is raised to 450 °C at 5 °C / min under inert atmosphere protection in a high-temperature furnace, and kept warm for 2 h; the temperature is further raised to 1400 °C at 2 °C / min, and kept warm for 2 h to complete carbonization; the carbonized composite bipolar plate sample is immersed in impregnating asphalt (quinoline insoluble content is 0.1%, and softening point is 85 °C), placed in a vacuum drying oven, immersed at 110 °C and 10 kPa negative pressure for 5 h, and the residual asphalt on the surface is cleaned with ethanol solvent, and then placed in a heating furnace and heated to 400 °C. After 2 h of heat preservation, the ceramic and carbonaceous reinforced carbon-based composite bipolar plate material is obtained to complete curing.

[0026] Example 7 This embodiment provides a method for preparing a ceramic and carbonaceous reinforced carbon-based composite bipolar plate material. The difference from Example 2 is that no impregnation curing is performed, and other conditions are the same as those in Example 2.

[0027] Example 8 This embodiment provides a method for preparing a ceramic and carbonaceous reinforced carbon-based composite bipolar plate material. The difference from Example 2 is that no asphalt modifier (phenolic resin) is added, and other conditions are the same as those in Example 2.

[0028] Example 9 This embodiment provides a method for preparing a ceramic and carbonaceous reinforced carbon-based composite bipolar plate material. The difference from Example 2 is that titanium boride is replaced with an equal mass of titanium carbide, and other conditions are the same as those in Example 2.

[0029] Comparative Example 1 This comparative example provides a method for preparing a bipolar plate material, which differs from Example 2 in that firstly, medium-temperature coal tar pitch and an asphalt modifier (phenolic resin) are used for thermal polycondensation to generate a material containing asphalt intermediate phase spheres, which is then mixed with titanium boride, graphite and conductive graphite for subsequent hot pressing, sintering carbonization and impregnation treatment. Other conditions are the same as those in Example 2.

[0030] Comparative Example 2 This comparative example provides a method for preparing a bipolar plate material, which differs from Example 2 in that the reinforcing phase material (15 g titanium boride with a particle size of 5 µm, 10 g graphite with a particle size of 5 µm, and 3 g conductive carbon black) is replaced with a mixture of boron carbide and silicon powder (14 g boron carbide and 14 g silicon powder), and other conditions are the same as those in Example 2.

[0031] Comparative Example 3 This comparative example provides a method for preparing a bipolar plate material, which differs from Example 2 in that, under the condition that the amount of reinforcing phase raw material added is the same, only titanium boride is used as the reinforcing phase, and other conditions are the same as those in Example 2.

[0032] Comparative Example 4 This comparative example provides a method for preparing a bipolar plate material, which differs from Example 2 in that, under the condition that the amount of reinforcing phase raw material added is the same, only carbonaceous material (17.5 g graphite, 10.5 g conductive carbon black) is used as the reinforcing phase, and other conditions are the same as Example 2.

[0033] Test Example 1 The compressive strength, resistivity and corrosion current density of the bipolar plate materials prepared in the above embodiments and comparative examples were tested, and the test results are shown in Tables 1 to 3 below. The compressive strength test method is as follows: a standard sample is prepared. Φ After the thickness is 45 mm × 45 mm, the compressive strength test is carried out at a constant loading rate of 1 kN / s (the ultimate strain is the maximum strain value corresponding to the failure of the compressive strength, and the calculation formula is: ε =Δ L / L 0 ;in, ε is the ultimate strain, Δ L is the maximum compression before the material breaks, L 0 is the original length of the material); the resistivity test method is: the resistivity test is carried out using the four-probe method (the standard sample size is 50 mm×50 mm×4 mm); the corrosion current density test method is: the sample (size is Φ The Tafel curve test was carried out in a 0.5 mol / L sulfuric acid solution with a scanning rate of 0.1 mV / s using a platinum sheet as the counter electrode.

[0034] Table 1

[0035] Table 2

[0036] Table 3

[0037] According to Tables 1 to 3, the compressive strength of the bipolar plate materials prepared in Examples 1 to 9 of the present invention is between 102.2 MPa and 145.3 MPa, the ultimate strain is between 5.9% and 7.1%, and the resistivity is between 4.25×10 -6 Ω·m~10.22×10 -6 Ω·m, corrosion current density is between 5.5 μA / cm 2 ~21.2 μA / cm 2 The obtained bipolar plate material has excellent mechanical properties, electrical conductivity and corrosion resistance.

[0038] Compared with Examples 1 to 9, the compressive strength of the ceramic and carbonaceous reinforced carbon-based composite bipolar plate material prepared by non-in-situ coating of the reinforcing phase in Comparative Example 1 is only 88.6 MPa, and the resistivity is as high as 23.22×10 -6 Ω·m; Comparative Example 2 uses boron carbide and silicon powder as reinforcement phases, and the obtained carbon-based composite bipolar plate material has excellent compressive strength, but the resistivity (up to 80.41×10 -6 Ω·m) and corrosion current density (up to 55.2 μA / cm 2 ) are relatively high; Comparative Example 3 uses only titanium boride as a reinforcement phase without adding a carbonaceous reinforcement phase, and the conductivity of the carbon-based composite bipolar plate material obtained is poor (the resistivity is 44.21×10 -6 Ω·m); Comparative Example 4 uses only carbonaceous material as a reinforcement phase without adding a ceramic reinforcement phase. The mechanical properties, electrical conductivity and corrosion resistance of the carbon-based composite bipolar plate material are poor (the compressive strength is only 89.5 MPa and the resistivity is as high as 26.37×10 -6 Ω·m, corrosion current density up to 64.7 μA / cm 2 ).

[0039] Compared with Example 2, Examples 7 to 9 respectively adopt the methods of not performing impregnation curing, not adding asphalt modifier, and replacing titanium boride with an equal mass of titanium carbide ceramic reinforcement phase. The mechanical properties, electrical conductivity and corrosion resistance of the carbon-based composite bipolar plate materials obtained are reduced to a certain extent, but the effects are still significantly better than the carbon-based composite bipolar plate materials obtained in Comparative Examples 1 to 4.

[0040] Obviously, the above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from them are still within the protection scope of the invention.

Claims

1. A method for preparing a ceramic and carbonaceous reinforced carbon-based composite bipolar plate material, characterized in that: include: The ceramic reinforcement phase, the carbonaceous reinforcement phase and the asphalt compound are mixed as raw materials and subjected to thermal polycondensation reaction, and the asphalt intermediate phase carbon microspheres in-situ coated with ceramic and carbonaceous reinforcement phase precursors are obtained through solvent extraction and solid-liquid separation; In-situ coating of the pitch mesophase carbon microspheres with ceramic and carbonaceous reinforcement phase precursors is performed by hot pressing to obtain a green body; The green body is subjected to sintering carbonization treatment and impregnation treatment to obtain ceramic and carbonaceous reinforced carbon-based composite bipolar plate material.

2. The preparation method according to claim 1, characterized in that: The asphalt compound includes at least one of coal asphalt, petroleum asphalt, naphthalene asphalt, and secondary refined asphalt; And / or, the carbonaceous reinforcement phase includes at least one of graphite, expanded graphite, carbon black, carbon fiber, and graphene; and / or, the particle size of the carbonaceous reinforcement phase is 0.02-10 µm; And / or, the ceramic reinforcement phase includes at least one of titanium boride, titanium carbide, titanium nitride and boron carbide; And / or, the particle size of the ceramic reinforcement phase is 0.1-10 µm; And / or, the mass ratio of the asphalt compound, the ceramic reinforcement phase and the carbonaceous reinforcement phase is 20:(1-6):(0.1-3).

3. The preparation method according to claim 1 or 2, characterized in that: The mixing process is: treating at a temperature of 120-180°C and a stirring rate of 1500-2500 r / min for 0.5-2 h; And / or, the temperature of the thermal polycondensation reaction is 380-420°C; And / or, the heating rate of the thermal polycondensation reaction is 1-5°C / min; And / or, the stirring rate of the thermal polycondensation reaction is 300-800 r / min; And / or, the duration of the thermal polycondensation reaction is 2 to 4 hours; And / or, the atmosphere of the thermal polycondensation reaction is an inert atmosphere; And / or, an asphalt modifier is also added during the thermal polycondensation reaction; and / or, crushing is performed after the thermal polycondensation reaction; and / or, the organic solvent used in the solvent extraction includes at least one of tetrahydrofuran, toluene, pyridine, quinoline, dichloromethane, trichloroethylene, and washing oil; And / or, the solid-liquid separation includes at least one of filtration, sedimentation, and centrifugation.

4. The preparation method according to claim 3, characterized in that: The asphalt modifier is a resin-based modifier; And / or, the mass ratio of the asphalt modifier to the asphalt compound is (0.5~4):

20.

5. The preparation method according to claim 1 or 2, characterized in that: The molding temperature of the hot pressing molding is 320-380°C; And / or, the molding pressure of the hot pressing molding is 30-80 MPa; And / or, the stabilization time of the hot pressing molding is 8 to 15 minutes; And / or, screening treatment is further performed before the hot pressing forming.

6. The preparation method according to claim 1 or 2, characterized in that: The sintering and carbonization process is as follows: firstly, the temperature is raised to 400-450°C at a rate of 1-5°C / min and kept at that temperature for 1-2 hours, and then the temperature is further raised to 900-1400°C at a rate of 1-2°C / min and kept at that temperature for 2-5 hours; And / or, the atmosphere of the sintering and carbonization treatment is an inert atmosphere.

7. The preparation method according to claim 1 or 2, characterized in that: The impregnating agent used in the impregnation process is a thermosetting phenolic resin and / or asphalt; And / or, the impregnation treatment is carried out under negative pressure conditions; And / or, the immersion treatment time is 5 to 10 hours; and / or, washing with an organic solvent after the immersion treatment; And / or, the impregnation treatment is further followed by a curing treatment.

8. The preparation method according to claim 7, characterized in that: The negative pressure condition is 0.1~10 kPa; And / or, the organic solvent includes at least one of ethanol and acetone; And / or, when the impregnating agent is a thermosetting phenolic resin, the curing temperature is 160-190° C., and the curing time is 1-2 h; And / or, when the impregnating agent is asphalt, the content of asphalt quinoline insoluble matter is not greater than 0.1%, the softening point is 50-100°C, the temperature of the impregnation treatment is 100-120°C, the temperature of the curing treatment is 380-420°C, and the time of the curing treatment is 2-3 h.

9. Ceramic and carbonaceous reinforced carbon-based composite bipolar plate material, characterized in that: It is prepared by the preparation method of the ceramic and carbonaceous reinforced carbon-based composite bipolar plate material described in any one of claims 1 to 8.

10. Application of the ceramic and carbonaceous reinforced carbon-based composite bipolar plate material according to claim 9 in fuel cells and water electrolysis hydrogen production stacks.

Citation Information

Patent Citations

  • Core-shell structure silicon / mesocarbon microbead composite negative electrode material and preparation method thereof

    CN110931747A

  • Mesocarbon microbeads, graphite anode material, preparation methods thereof, and lithium ion battery

    CN112054165A

  • Silicon carbide / boron carbide ceramic skeleton reinforced carbon-based composite material as well as preparation method and application thereof

    CN116396090A

  • Mesocarbon microbead-based bipolar plate material as well as preparation method and application thereof

    CN116722165A

  • Asphalt-based graphite composite material as well as preparation method and application thereof

    CN118867169A

Cited By

  • Preparation process of high-strength ultrahigh-power graphite electrode

    CN121627407A

  • A nanometer silicon / mesocarbon microbead composite material, a preparation method and application thereof

    CN122599423A